2007
DOI: 10.1002/ijc.22320
|View full text |Cite
|
Sign up to set email alerts
|

The effects of combined antioxidant (β‐carotene, α‐tocopherol and ascorbic acid) supplementation on antioxidant capacity, DNA single‐strand breaks and levels of insulin‐like growth factor‐1/IGF‐binding protein 3 in the ferret model of lung cancer

Abstract: Insulin‐like growth factor 1 (IGF‐1) and its major binding protein, IGF binding protein 3 (IGFBP‐3) are implicated in lung cancer and other malignancies. We have previously shown that the combination of three major antioxidants [β‐carotene (BC), α‐tocopherol (AT) and ascorbic acid (AA)] can prevent lung carcinogenesis in a 4‐(methylnitrosamino)‐1‐(3‐pyridyl)‐1‐butanone (NNK)‐treated and smoke‐exposed (SM) ferret model, which is highly analogous to humans. The present study is aimed at determining the effect of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
1
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 53 publications
0
26
1
1
Order By: Relevance
“…As potent antioxidants, carotenoids can deactivate free radicals that damage the basic structure of cells and thus lead to cancer (40). However, carotenoids were not detected in the GS-DDG lipid sample under the conditions of the test and thus could not account for the cited antiproliferation results.…”
Section: Resultscontrasting
confidence: 48%
“…As potent antioxidants, carotenoids can deactivate free radicals that damage the basic structure of cells and thus lead to cancer (40). However, carotenoids were not detected in the GS-DDG lipid sample under the conditions of the test and thus could not account for the cited antiproliferation results.…”
Section: Resultscontrasting
confidence: 48%
“…2). Since we have previously shown that NNK and cigarette smoke treatment resulted in increased ERK activation [37] and proliferating cellular nuclear antigen [31, 38-40], this could be due to the limited sample size or NNK treatment alone (without smoke exposure) in the present study. It has been reported that the expression of α7 nAChR was related to the major activation of the Rb-Raf-1/phospho-ERK pathway and was associated with proliferation of lung cancer cells [34, 41].…”
Section: Discussionmentioning
confidence: 86%
“…According to Cassano et al (19991, oxidative damage to the oocyte or Table 1 Least square means for body weight (BW), body condition score (BCS), total follicles (FT), total corpus luteum (CLT) and total ovarian activity (TOA=FT+CLT) in goats supplemented with betacorotene (BETA, 50 mg goat-' day-l) and no supplemented goats (CONTROL) In fact, betacarotene acts against lipid peroxidation as a n antioxidant molecule protecting several reproductive structures from oxidative DNA-damage (Kim et al, 2007). Betacarotene seems to act as a n ovarian-protective molecule, not only as luteoprotective (Haliloglu et al, 2002) but also improving embryo production a n d quality in superovulated cows (Sales et al, 2007), optimizing reproductive performance in females.…”
Section: Resultsmentioning
confidence: 99%